Analisis Pelaksanaan Timbang Terima Pasien di ruang Perawatan RSUD Otanaha Kota Gorontalo - Euis H. Hidayat; Anita Asih (Pusat Riset dan Inovasi Nasional, 2023)
Handover is a technique or way of conveying and receiving something (report) related to the client's condition. purpose of this research is to analyze the balance of acceptance. This study used observational and chi-square research designs with a weigh-in analysis approach. With 12 nurses. This study uses data collection procedures by observing and documenting. Based on the results of the study it was found that those who answered Do = 10%. While those who answered Not Done = 15.9%.